Ocean fishing: Economic efficiency and the law of the sea - Wilfried Prewo (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1979)
The legitimation of the freedom of fishing as the principle guaranteeing open, i.e., unconstrained and non-priced access to the oceans' living resources was in great part based on the premise that these resources are inexhaustible, that their use does not diminish their value. These observations were central to Hugo Grotius' writings on the freedom of fishing. ... all that which has been so constituted by nature that although serving some one person it still suffices for the common use of all other persons, is today and ought in perpetuity to remain in the same condition as when it was first created by nature. And, to reaffirms: For by using, the sea itself is not at all impaired, and it needs no cultivation to bear fruit. Therefore, the sea deservedly remained common. For three centuries following the writings of Grotius, open access to fisheries continued to be the practical solution even though the presumption of inexhaustibility grew doubtful. Open access, as it turns out,, was practical, not because ocean resources were free goods lacking any degree of scarcity, but because the benefits to be gained from limiting access and extending jurisdiction over the oceans did not justify the costs of establishing and enforcing an exclusive access system. First; rudimentary fishing techniques had, through the relation of cost to price, lir.ited harvesting to levels which air not seriously affect the stocks' reproductive potentials, thus making then appear inexhaustible. Second^ enforcement of exclusive jurisdiction;, if at all technically feasible, would have entailed disproportionate costs. Such costs have played a major role in the historical development of the Law of the Sea. A prime example is the seaward extension of the territorial sea to three miles, which, as is often said, corresponded to the range of a cannon.
Keywords: 330